The Chicano Feminist Identity and Cultural Conflict in Sanchez’s I’m Not The Perfect Mexican Daughter - Kasih, E. Ngestirosa Endang Woro; Wardaningsih, Agustin Diana; Putra, Ahmad Vahry Lilam (Journal of Feminism and Gender Studies, 2024)
This research delves into feminist themes within the novel "I'm not the Perfect Mexican Daughter," focusing on the depiction of women through the perspectives of two key female characters. Employing feminist literary analysis, the study investigates how Chicana women are represented in a society entrenched in patriarchal norms. Drawing from Garcia’s Chicana feminist and Tong’s feminist theories, it argues that women occupy subordinate positions due to entrenched male dominance. Despite advancements in the public sphere, Chicano women are still expected to adhere to traditional family roles, being judged primarily on physical appearance. Men are portrayed as dominant figures, wielding power in economic and social realms. Through the lives of the main characters, the novel highlights the challenges and contradictions faced by Chicana women amidst the women's movement. It presents an idealized image of womanhood emblematic of Chicana experiences in the United States, exploring Julia's defiance of gender norms, Olga's complex negotiation between conformity and rebellion, and Ama's struggle with societal expectations.